Si@SiOx/Graphene Nanosheets Composite: Ball Milling Synthesis and Enhanced Lithium Storage Performance - Tie, Xiaoyong; Han, Qianyan; Liang, Chunyan; Li, Bo; Zai, Jiantao; Qian, Xuefeng (Frontiers in Materials, 2018)
Si@SiOx/grapheme nanosheet (Si@SiOx/GNS) nanocomposites as high-performance anode materials for lithium-ion batteries are prepared by mechanically blending the mixture of expanded graphite (EG) with Si nanoparticles, and characterized by Raman spectrum, X-ray diffraction (XRD), field emission scanning electron microscopy, and transmission electron microscopy. During ball milling process, the size of Si nanoparticles will decrease, and the layer of EG can be peeled off to thin multilayers. Electrochemical tests reveal that the Si@SiOx/GNS nanocomposites show enhanced cycling stability, high reversible capacity, and rate capability, even with high content of active materials of 80% and without electrolyte additives. The retained revisable capacity is 1,055 mAh g−1 after 50 cycles at 0.2 A g−1 and about 63.6% of the initial value. The great electrochemical performance of Si@SiOx/GNS nanocomposites can be ascribed to GNS prepared through heat-treat and ball-milling methods, the decrease in the size of Si nanoparticles and SiOx layer on Si surface, which enhance the interactions between Si and GNS.